A novel time-aware attention-enhanced transformer to prediction harmful algal Bloom's occurrence - Liye Song; Shengjun Xu; Jingyu Lin; Zhihui Bai (Marine Pollution Bulletin, 2026)

Integrating aquatic crops into rotation systems enhances soil health and suppresses potential fungal pathogens in greenhouse cucumber production - Jun Xu; Zhuoya Zhao; Liu Pan; Yuan Yao; Zhi Li; Yurui Wang; Yanfeng Li; Xuehao Chen (Applied Soil Ecology, 2026)

Asparagus Polysaccharide Ameliorates TNF-α-Mediated MH7A Cell Dysfunction and Collagen-Induced Arthritis in Mice - Mingfeng Yang; Fangyan Xu; Bin Zhang; Lijun Xu (Cell Biochemistry and Biophysics, 2026)

GNSS ultra-rapid clock offset prediction with the aid of sparse modeling on satellite clock frequency - Chao Hu; Tianjun Xu; Lei Wang; Changpeng Tao; Tong Cheng; Zhongchen Guo (Acta Geodaetica et Geophysica, 2026)

Temperature-dependent proteomic profiling of outer membrane vesicles reveals virulence-associated protein enrichment in Pseudomonas plecoglossicida - Yuejiangbo Liu; Min Jiang; Xia Si; Chaozheng Zhang; Jianjun Xie; Wei Wang; Gengshen Wang; Wenjun Xu (Aquaculture, 2026)

Native earthworms maintain their environmental functionality following deforestation - Tangjun Xu; Yu Fang; Hongyi Liu; Gaoji Zhang; Yufeng Zhang; Xiaoming Zou; Manuel Delgado-Baquerizo; Honghua Ruan (Applied Soil Ecology, 2025)

Bacillus-loaded biochar as a dual strategy for Fusarium wilt control and soil health improvement in Peanut cultivation - Qibiao Li; Yonghua Hu; Xuejiao Zhang; Lei Xu; Zhijun Xu (Applied Soil Ecology, 2025)

Phosphorus fertilization reduction enhanced legacy P recovery in an Ultisol under maize-soybean intercropping system: Implication for soil health and green crop production - Jin Liu; Yuhang Zhao; Dongling Yang; Jun Xu; Jianjun Yang (Applied Soil Ecology, 2024)

What determines the time lags of sap flux with solar radiation and vapor pressure deficit? - Liuliu Wan; Quan Zhang; Lei Cheng; Yujie Liu; Shujing Qin; Jijun Xu; Yongqiang Wang (Agricultural and Forest Meteorology, 2023)

MicroRNA regulation of Toll‐like receptor, RIG‐I‐like receptor and Nod‐like receptor pathways in teleost fish - Qing Chu; Tianjun Xu (Reviews in Aquaculture, 2020)
The innate immune system is the first‐line defence against invading pathogens, and the main molecules involved in recognizing invading pathogens are the pattern recognition receptors. Accumulating evidences have demonstrated that activation and termination of the immune responses are regulated by various layers of regulators and mechanisms. MicroRNAs (miRNAs) are a group of small non‐coding RNAs that emerged as critical component of the complex regulatory networks in fish immune responses. In this review, we have summarized miRNA regulation in teleost fish, which can provide new insights into the regulation of innate immune receptor pathways in fish. Meanwhile, we comprehensively discuss the recent researches on how teleost miRNAs respond to the signalling pathways of innate immune receptors, including Toll‐like receptors, retinoic acid‐inducible gene‐I‐like receptors and Nod‐like receptors.

Composition, diversity, and environmental correlates of benthic macroinvertebrate communities in the five largest freshwater lakes of China - Yongjiu Cai; You Zhang; Zhaoshi Wu; Yuwei Chen; Jun Xu; Zhijun Gong (Hydrobiologia, 2017)